Therapeutic Drug Monitoring of the Newer Anti-Epilepsy Medications - Matthew D. Krasowski (MDPI AG, 2010)
In the past twenty years, 14 new antiepileptic drugs have been approved for use in the United States and/or Europe. These drugs are eslicarbazepine acetate, felbamate, gabapentin, lacosamide, lamotrigine, levetiracetam, oxcarbazepine, pregabalin, rufinamide, stiripentol, tiagabine, topiramate, vigabatrin and zonisamide. In general, the clinical utility of therapeutic drug monitoring has not been established in clinical trials for these new anticonvulsants, and clear guidelines for drug monitoring have yet to be defined. The antiepileptic drugs with the strongest justifications for drug monitoring are lamotrigine, oxcarbazepine, stiripentol, and zonisamide. Stiripentol and tiagabine are strongly protein bound and are candidates for free drug monitoring. Therapeutic drug monitoring has lower utility for gabapentin, pregabalin, and vigabatrin. Measurement of salivary drug concentrations has potential utility for therapeutic drug monitoring of lamotrigine, levetiracetam, and topiramate. Therapeutic drug monitoring of the new antiepileptic drugs will be discussed in managing patients with epilepsy.